Integration of Borehole and Surface Seismic Monitoring Techniques in CO2 Geosequestration Projects - Popik, Sofya (Curtin University, 2021)
This thesis is focused on utilisation of both borehole and surface seismic techniques to improve monitoring effectiveness in CO2 geosequestration projects based on data acquired within the CO2CRC Otway Project. The study includes processing and analysis of 4D surface seismic data with buried receiver array, investigation of optimal source effort required to image time-lapse anomaly, and analysis of multiple 3D VSP datasets for the purpose of building anisotropic velocity model of the Otway Site.